Valorization of banana peels to obtain a bioplastic from acetylated starch - Llatance Mujica, Fiorella (2025)
Global solid waste generation will increase by 70% by 2050. Within this projection, organic waste will constitute 44% of the total. Among these organic wastes are banana peels, which can be valorized to be transformed into bioplastic. The objective of this research is to develop a bioplastic film on a laboratory scale, from the starch extracted from banana peels using the acetylation method. To evaluate the quality of the bioplastic, six tests were carried out modifying the residence time, the ripening of the banana peels, the pH and the concentration of glycerin. To evaluate the quality of the bioplastic obtained, biodegradability tests, tensile tests and Fourier transform infrared spectroscopy (FTIR) were carried out. The results obtained revealed an 80% efficiency in the conversion of banana peels to bioplastic. The percentage of biodegradability reached a maximum percentage of 47%, highlighting the influence of the amount of glycerin used in the process. In terms of tensile strength, values of 3.169 MPa were recorded, while the Young's modulus was 0.486 MPa. Fourier Transform Infrared Spectroscopy (FT-IR) analysis indicated the presence of functional groups characteristic of starch molecules such as Carbon - Hydrogen (CH), Hydroxyl Radical (OH), Carbon Monoxide (CO) characteristic of starch molecules.